The Cornea Has "the Nerve" to Encourage Immune Rejection. Issue 6 (14th April 2015) - Blanco, T.; Saban, D. R.
<x xml:space="preserve">Abstract</x> The study by Paunicka et al (page 1490) forces transplantation immunologists to consider the interplay between the nervous and immune systems as yet another piece of the perplexing puzzle that is immune rejection.